Core hyper-cross-linked star polymers from block polymer micelle precursors. Issue 45 (2nd November 2020) - Park, Jongmin; Smith, Stefan J. D.; Wood, Colin D.; Mulet, Xavier; Seo, Myungeun
Abstract : Hyper-cross-linking of a core of block polymer micelles produces core cross-linked polymer with a spacious hyper-cross-linked core, which is solution-processible. Abstract : This study explores hyper-cross-linking of the cores of block copolymer micelles as a means to generate star polymers with a hyper-cross-linked core surrounded by linear corona arms. A solution of poly(methyl methacrylate)- b -polystyrene (MS) was prepared in acetonitrile to form micelles which were reacted with α, α′-dichloro- p -xylene in the presence of FeCl3 to produce core hyper-cross-linked star (CHS) polymers by selective cross-linking of the PS core. A kinetic investigation showed formation of high-molar mass species (>10 4 kg mol −1 ) within 1 h of reaction, which supported conversion of individual MS micelles into CHS polymers. We synthesized several CHS polymers by varying the PS core fractions from 20 to 53%. All the polymers possessed discrete spherical cores that were 19–60 nm in diameter and all were highly soluble in organic solvents retaining the CHS architecture. While permanent microporosity was not detected by gas sorption measurements, increased dye uptake of CHS polymer in solution suggests utility of CHS polymers as stable and solution-processible nanocontainers with accessible free volume in the core.